Correlation between compressive strength and fire resistant performance of rice husk ash-based geopolymer binder for panel applications - Mohd Basri, Mohd Salahuddin; Mazlan, Norkhairunnisa; Mustapha, Faizal; Ishak, Mohamad Ridzwan (EDP Sciences, 2016)
Panel structures which are mainly used as insulation materials should possess high fire resistance characteristic. In addition, their mechanical requisites for walls and doors such as compressive strength must not be unduly compromised. Rice husk ash (RHA) was used as an aluminosilicate source and two factors namely RHA/AA ratio and NaOH concentration were analyzed using statistical tool to study the effect of both factors on the compressive strength. Surface morphology and fire resistant behavior of four selected samples based on their compressive strength (brittle, semi-brittle, ductile, and semi-ductile samples) were studied to determine the correlation between compressive strength and fire resistant performance of those selected samples. Results showed that RHA-based geopolymer sample recorded high compressive strength above 28 MPa when its RHA/AA ratio and NaOH concentration were high ranging from 0.7 to 0.8 and 12M to 14M, respectively. Brittle geopolymer sample (GS) with low Si/Al ratio shows high compressive strength together with high degree of geopolymerization. Ductile GS in comparison, shows low compressive strength irrespective of its degree of geopolymerization. Semi-ductile GS showed the best fire resistant properties with a maximum non-exposed surface temperature of only 50°C after 50 minutes (after it was exposed to a direct fire with temperature of 900°C) followed by semi-brittle and brittle GS.